Systematic Evaluation of Physical Parameters Affecting the Terminal Settling Velocity of Microplastic Particles in Lakes Using CFD - Ahmadi, Pouyan; Elagami, Hassan; Dichgans, Franz; Schmidt, Christian; Gilfedder, Benjamin S.; Frei, Sven; Peiffer, Stefan; Fleckenstein, Jan H. (Frontiers in Environmental Science, 2022)
Microplastic (MP) particles are commonly found in freshwater environments such as rivers and lakes, negatively affecting aquatic organisms and potentially causing water quality issues. Understanding the transport and fate of MP particles in these environments is a key prerequisite to mitigate the problem. For standing water bodies (lakes, ponds) the terminal settling velocity (TSV) is a key parameter, which determines particle residence times and exposure times of organisms to MP in lakes. Here we systematically investigate the effects of the physical parameters density, volume, shape and roundness, surface roughness and hydrophobicity and lake water temperature on the TSV of a large number of particles with regular and irregular shapes (equivalent diameters: 0.5 to 2.5mm) and different polymer densities using computational fluid dynamics (CFD) simulations. Simulation results are compared to laboratory settling experiments and used to evaluate existing, semi-empirical relationships to estimate TSV. The semi-empirical relationships were generally found to be in reasonable agreement with the CFD simulations (R2 > 0.92). Deviations were attributed to simplifications in their descriptions of particle shapes. Overall the CFD simulations also matched the TSVs from the experiments quite well, (R2 > 0.82), but experimental TSVs were generally slower than model TSVs with the largest differences for the irregular particles made from biodegradable polymers. The deviations of up to 58% were found to be related to the attachment of air bubbles on irregularities in the particle surfaces caused by the hydrophobicity of the MP particles. Overall, density was the most decisive parameter for TSV with increases in TSV of up to 400% followed by volume (200%), water temperature (47%) and particle roundness (45%). Our simulation results provide a frame of reference for an improved evaluation of the relative effects of different particle characteristics on their TSV in lakes. This will in turn allow a more robust estimation of particle residence times and potential exposure times of organism to MP in the different compartments of a lake.